2016
DOI: 10.1097/meg.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Short article: Faldaprevir, deleobuvir and ribavirin in IL28B non-CC patients with HCV genotype-1a infection included in the SOUND-C3 phase 2b study

Abstract: In this small study, the interferon-free regimen of faldaprevir, deleobuvir and ribavirin resulted in high rates of virological breakthrough and low rates of SVR12 in IL28B non-CC genotype patients infected with genotype-1a HCV (http://www.clinicaltrials.gov NCT01132313).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…These patients were treated with SOF/RBV + Peg-INF regimen and it was reported that SVR rate was 99% in subjects with CC genotype and 87% in subjects with non-CC genotypes [ 4 ]. Also, in patients with IL28B non-CC genotype and infected with HCV-1a, Peg-INF-free regimens included combination of deleobuvir, faldaprevir, and ribavirin resulted in low SVR rates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients were treated with SOF/RBV + Peg-INF regimen and it was reported that SVR rate was 99% in subjects with CC genotype and 87% in subjects with non-CC genotypes [ 4 ]. Also, in patients with IL28B non-CC genotype and infected with HCV-1a, Peg-INF-free regimens included combination of deleobuvir, faldaprevir, and ribavirin resulted in low SVR rates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%